Review of the Pharmacological Properties and Phytochemical Profile of Ptaeroxylon obliquum (Thunb.) Radlk - Kim, Jinwoo; Cock, Ian Edwin; Cheesman, Matthew James (Pharmacognosy Communications)
Introduction: Ptaeroxylon obliquum (Thunb.) Radlk. That is a medium tree native to South Africa. It has been traditionally used for centuries to treat a wide range of disorders. Objectives: This study reviews the pharmacological profile of South African Ptaeroxylon obliquum (Thunb.) Radlk., including its ethnobotanical use, anti-inflammatory, anti-microbial, and anti-proliferative bioactivities, with the aim of encouraging additional research in this field. Materials and Methods: Scientific literature, review articles, and online databases were examined to investigate traditional therapeutic applications of P. obliquum. A subsequent search was carried out to identify studies examining the pharmacological properties of P. obliquum. Results: The review highlighted the therapeutic properties of P. obliquum, including significant antimicrobial activity against a panel of bacterial and fungal pathogens. This species also has anti-inflammatory properties, including inhibition of COX-2, reducing pro-inflammatory cytokine secretion, and modulation of NF-ΚB transcription pathways. Additionally, anti-proliferative activity has been observed against specific cancer cell lines, although relatively few studies have explored this potential. Conclusion: Whilst Ptaeroxylon obliquum has promising pharmacological properties, including antibacterial, antifungal, anti-inflammatory and anticancer effects, its mechanisms of action, and toxicity have been relatively poorly studied. Future studies are required to identify the active compounds, evaluate the therapeutic efficacy in vivo, and expand research into its anticancer potential.
Keywords: Traditional Medicine; Sneezewood; Rutaceae; Anti-inflammatory activity; Antibacterial activity; Anticancer activity.